The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s10803-016-2988-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-Parenting Quality, Parenting Stress, and Feeding Challenges in Families with a Child Diagnosed with Autism Spectrum Disorder

Abstract: 113 parents of children aged 5-13 with ASD completed online surveys assessing co-parenting quality, parenting stress, and child feeding challenges. Results indicated that food selectivity was both the most frequently reported type of challenging feeding behavior and the most often reported as problematic but was also the only type of challenging feeding behavior that was not associated with parenting stress. Greater parenting stress was reported when co-parenting agreement and support were lower. Child disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 44 publications
2
42
0
3
Order By: Relevance
“…Previous research has highlighted the negative impact that eating difficulties can have on pupils within the educational setting (Koenig and Rudney, 2010). In line with previous studies that have shown a strong correlation between mealtime behavior and parental stress and a negative impact on family life (Kerwin et al, 2005;Bagby et al, 2012;Suarez et al, 2014a;Postorino et al, 2015;Thullen and Bonsall, 2017), parents have themselves identified their child's diet as a priority area for support (Galpin et al, 2017). The aim of the current study was, therefore, to examine the impact of a sensory based intervention to address food selectivity in autistic pupils that could be delivered in a school setting by teaching staff.…”
Section: Aimsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous research has highlighted the negative impact that eating difficulties can have on pupils within the educational setting (Koenig and Rudney, 2010). In line with previous studies that have shown a strong correlation between mealtime behavior and parental stress and a negative impact on family life (Kerwin et al, 2005;Bagby et al, 2012;Suarez et al, 2014a;Postorino et al, 2015;Thullen and Bonsall, 2017), parents have themselves identified their child's diet as a priority area for support (Galpin et al, 2017). The aim of the current study was, therefore, to examine the impact of a sensory based intervention to address food selectivity in autistic pupils that could be delivered in a school setting by teaching staff.…”
Section: Aimsupporting
confidence: 75%
“…Disruptive Mealtime Behaviours and Food Refusal scores had also significantly reduced. In light of the impact that difficulties in these areas can have upon family life, notably parenting stress (Kerwin et al, 2005;Bagby et al, 2012;Suarez et al, 2014a;Postorino et al, 2015;Thullen and Bonsall, 2017) these results are particularly encouraging. Parents of autistic children have identified diet and eating as a priority area for support for them and their children (Galpin et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…May et al . 2015; Thullen and Bonsall 2017). Although mothers and fathers experience similar high levels of parenting stress, fathers' stress levels were more closely tied to the quality of the co‐parenting relationship.…”
Section: Fathers Of Children With Autism Spectrum Disordermentioning
confidence: 99%
“…Esse resultado é muito relevante para o equilíbrio das relações estabelecidas no microssistema familiar, porque geralmente o cuidado do filho com TEA é atribuído ao maior nível de estresse parental e, consequentemente, uma relação parental negativa com maiores níveis de conflito e desacordo (Hill-Chapman et al, 2013;Sim et al, 2017). Ao longo do tempo é necessário um equilíbrio nas práticas parentais dos pais e isso depende da capacidade deles para gerenciar o estresse e trabalhar em conjunto para manter alto nível de cuidados ao filho com TEA (Thullen & Bonsall, 2017).…”
Section: Subcategoria: Acordo Nas Práticas Parentaisunclassified
“…No âmbito internacional se destacam alguns estudos sobre o tema com os pais de crianças com TEA, mas todos eles aplicaram escalas e utilizaram de abordagens quantitativas e também encontram resultados semelhantes, no qual relacionam que quanto maior o estresse parental menor será a qualidade na relação coparental (Hill-Chapman, Herzog, & Maduro, 2013;May, Fletcher, Dempsey, & Newman, 2015;Thullen & Bonsall, 2017). O estresse parental é mais elevado nas mães influenciado pela percepção que elas têm sobre a desigualdade na divisão das tarefas parentais (Bonis, 2016).…”
Section: Introductionunclassified